reaMy dad's got an alligator - Strong, Jeremy (London : Puffin, 2007)
Some dads bring home rabbits, or dogs, or parrots. Not Nichola's dad. The latest member of their family is Cranchbag -the ALLIGATOR!
Keywords: Alligators -- Fiction; Dads and sons -- Fiction; Pets -- Fiction